Constitutive expression of 8-lipoxygenase in papillomas and clastogenic effects of lipoxygenase-derived arachidonic acid metabolites in keratinocytes - Bürger, Friederike; Krieg, Peter; Schurich, Bärbel; Marks, Friedrich; Fürstenberger, Gerhard (Molecular carcinogenesis, 1999)
The expression pattern, enzymatic activity, and products of 8-lipoxygenase (LOX) were analyzed in normal and neoplastic skin of NMRI mice. While barely detectable in normal epidermis, 8-LOX was transiently induced by 12-O-tetradecanoylphorbol-13-acetate and constitutively expressed in papillomas but not carcinomas obtained by the initiation-promotion protocol of mouse skin carcinogenesis. The product profile and chirality of both the native and the recombinant protein produced the S enantiomers of 8-hydroxy-5Z,9E,11Z,14Z-eicosatetraenoic acid (8-HETE) and 9-hydroxy-10E,12Z-octadecadienoic acid (9-HODE) as the main arachidonic acid- and linoleic acid-derived metabolites. As compared with normal epidermis, papillomas exhibited 25- and 4-fold elevated levels of 8-HETE and 9-HODE, respectively. However, the varying S to R ratios of 8-HETE and the predominance of 9(R)-HODE indicated that in addition to 8(S)-LOX, other enzymes yet to be defined may be involved in 8-HETE and 9-HODE production. The massive accumulation of both 8-HETE and 12-hydroxy-5Z,8Z,10E,14Z-eicosatetraenoic acid (12-HETE) point to a critical role of these LOX pathways in epidermal tumor development, in particular in the papilloma stage. Here we showed that 8- and 12-hydroperoxyeicosatetraenoic acids and 8- and 12-HETE induce chromosomal alterations in cycling primary basal keratinocytes. Mol. Carcinog. 24:108-117, 1999. © 1999 Wiley-Liss, Inc.